Palladium chloride as seeding and surfactant layer to mediate the formation of top metal films on self-assembled monolayers - Chesneau, Frédérick; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2014)
Using self-assembled monolayers (SAMs) of [1,1′;4′,1″-terphenyl]-4,4″-dimethanethiol (TPDMT) on Au as a test system and nickel as a test adsorbate, we demonstrate that the penetration of deposited metal atoms into a SAM can be completely inhibited by the preliminary formation of palladium-chloride seeding layer at the SAM-ambience interface. This layer is formed by a simple dipping procedure that takes only a few minutes. The palladium atoms in the seeding layer serve as nucleation centers for the growing metal film, staying at its bottom during the growth. In contrast, the chlorine atoms are transferred from palladium to the deposited metal, staying on the top of the growing metal film and serving as surfactants. The above approach is a perspective way to solve the well-known top contact problem at the formation of metal-SAM-metal assemblies that are of potential importance for future electronic and spintronic devices.
Gesehen am 24.07.2020